CRITICAL ANALYSIS OF RESTITUTION BURDEN TO THE STATE (STUDY OF HERRY WIRAWAN) - Zuhdi, A Muflih El; Sulthanarafif, Teuku M; Maulia Dini, Dinda; Bagas, M Abid; Yuningsih, Henny (Faculty of Law Sriwijaya University, 2023)
The decision of the Bandung District Court sentenced the Ministry of Women's Empowerment and Child Protection of the Republic of Indonesia to be paid to 13 child victims of Defendant Herry Wirawan's rape. The decision was controversial in the community, then the public prosecutor filed an appeal at the Bandung High Court with a decision. This research aims to criticize the issue of imposing restitution on the state and legal protection for children against perpetrators of sexual violence who are unable to pay restitution. The type of research used is normative legal research with a statute approach using descriptive-qualitative analysis. The research results show that Bandung District Court Decision Number 989/Pid.Sus/2021/PN.Bdg was fallacious in considering terminology differences between restitution and compensation. On the other hand, Article 33 of Sexual Violence Crime Law reveals the state is obliged to provide compensation for the remaining amount of Restitution owed to Victims following a court decision through victim assistance funds. The study results are recommended in the victim and witness protection enforcement, although it should still refer to examination in the court.